2005
DOI: 10.1080/00365520510023332
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of postoperative peritoneal adhesions: Effects of lysozyme, polylysine and polyglutamate versus hyaluronic acid

Abstract: Lysozyme, polyglutamate and, most effectively, a polyglutamate-polylysine combination significantly decreased experimental abdominal adhesion formation. A strong mechanical connection to the wound and prolonged attendance in the surface were noted. Peritoneal phagocyte function did not seem to be influenced by the chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 17 publications
2
22
0
5
Order By: Relevance
“…We have previously shown that the combination of poly-L-lysine and poly-L-glutamate significantly reduces adhesions in an experimental model on abdominal adhesions 12 . Results from the former study and other pilot studies (data not published)…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We have previously shown that the combination of poly-L-lysine and poly-L-glutamate significantly reduces adhesions in an experimental model on abdominal adhesions 12 . Results from the former study and other pilot studies (data not published)…”
Section: Discussionmentioning
confidence: 95%
“…If so, more poly-L-lysine molecules can adhere to the wound, resulting in an accumulation of the poly-L-lysine/poly-L-glutamate exclusively at the wound site. The poly-L-lysine/poly-L-glutamate amount could rapidly be taken up and digested by phagocytes 12 , although their carrier function in the process is less probable considering the rapid development of the protecting layer (within 1day). This idea is supported by our findings that no visible residual compound was located anywhere else over the surrounding peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown no effect on local immunological functions, i.e. peritoneal macrophages, and a local clearance of this biodegradable matrix within 4 weeks [16,19]. The antiadhesive effect of the polypeptides is based on electrostatic binding between the strong cation poly-L-lysine and the negatively charged damaged peritoneum [29], and thereafter electrostatic bonds between the poly-L-lysine and the anion poly-L-glutamate create a mechanical barrier between damaged and adhesionprone peritoneal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The positively charged poly-L-lysine binds to the negatively charged damaged peritoneal surface and then attaches the negatively charged poly-Lglutamate to build a neutral matrix preventing adhesion formation [19]. In a recent study we questioned this combination due to the toxicity observed when the ani-mals were treated with α-poly-L-lysine alone [20].…”
Section: Introductionmentioning
confidence: 99%
“…Сочетание поли-L-лизин-поли-L-глутамат в экс-периментах предотвращает образование спаек с брюшиной без влияния на макрофаги, на прочность и герметичность анастомозов. В экспериментах вы-явлена также способность биоактивных полипепти-дов уменьшить кровотечение [4,21].…”
unclassified